Adoption of sustainable agricultural practices among smallholder dairy farmers in Malaysia: contributing factors and smart farming prospects - Rathakrishnan, Thanuja; Suntharalingamb, Chubashini; Lim, Yi Shern; Loong, Shih Keng; Lee, Hai Yen; Tee, Keng Kok; Sri Thanarajoo, Sathis; Balasundram, Siva K (Penerbit UiTM, 2022)
Adoption of Sustainable Agricultural Practices (SAP) among smallholder dairy farmers in developing countries, especially within the Asia Pacific region remains low. This is probably attributable to the fact that psycho-social factors are not considered during the adoption process. The current study was carried out in order to increase the adoption of SAP in Malaysia, by investigating psycho-social factors among dairy farmers. It adopted the enhanced Theory of Planned Behaviour to investigate smallholder dairy farmers’ intention to uptake SAP in Malaysia. This study applied the Partial Least Squares Structural Equation Modelling (PLS-SEM) to model how psycho-social factors influence farmers’ SAP adoption decisions. A key finding of this study was that farmers who are equipped with the right attitude and belief have the ability to adopt SAP and are inclined to adopt SAP in their farms. Hence, it was proposed that a holistic approach is recommended towards formulating policies and drawing intervention strategies that focus on the farmers’ needs and abilities. This would motivate farmers to make choices that would lead to a change of behaviour towards adopting SAP. Additionally, the producer-led approach adopted in this study provided insights into smallholder dairy farmers’ beliefs and behaviour.